Assessment of Liver Dysfunction Using Combination Biomarkers in Children Living with HIV Infection - Shalini Yadav; Rajeshwari Krishnan; Deepak Kumar (Galenos Yayinevi, 2022)
Aim:Overall, around 14-18% of non-acquired immunodeficiency syndrome-related deaths are due to liver disease in human immunodeficiency virus (HIV) patients. With a prevalence of 15%, cirrhosis appears to be a more serious consequence. There are many non-invasive markers for assessing liver fibrosis but their utility in pediatric HIV patients has not been explored.Materials and Methods:To assess the occurrence of liver dysfunction and the levels of combination biomarkers of liver dysfunction [aspartate aminotransferase (AST)/alanine aminotransferase (ALT) ratio, AST-to-platelet ratio index (APRI), and fibrosis-4 (FIB-4) index] in HIV positive children. A total of 44 HIV positive children aged <15 years attending the antiretroviral therapy (ART) clinic were enrolled and evaluated for liver dysfunction using non-invasive biomarkers and ultrasonography (USG) scoring.Results:Deranged biomarkers-AST/ALT ratios, APRI scores, and FIB-4 index were found in 95%, 6.8%, and 4.5% children respectively. 7% of children showed moderate to severe liver fibrosis on USG scoring. Also, anemia, nevirapine in ART regimen, longer ART duration, immunosuppression, and lower body mass index values were found as risk factors associated with deranged biomarkers.Conclusion:Hepatic dysfunction is reflected by deranged AST/ALT ratios among HIV-positive children in this study. Further, the elevated APRI scores and FIB-4 index in some cases signal evolving liver fibrosis.